Cambios en los hábitos de alimentación de los pobladores de Quito en el siglo XVIII después de la implementación de técnicas y productos gastronómicos europeos - Luzuriaga Marín, María Emilia (2017)
The gastronomy and diet of Quito habitants varied significantly with the Spanish people arrival, the introduction of European techniques and products that were easily adapt to climatic conditions determined a transformation in culinary preparations, which up to that time were determined by the close relationship between native indigenous and their environment. Spaniards diet in their origin place was decisive for the incorporation of products and techniques in the colonies, with the introduction of new products a change was generated, not only in the preparations, but also in the social, economic and political aspect. Along with this, the emergence of new ways of cooking this new products. The traditional cuisine of Quito is the result of a syncretism between products and techniques of the native and the European people, resulting in what is now known as traditional or Creole cuisine.